Ungkapan Kiasan Minangkabau di Desa Talawi Hilir Kecamatan Talawi Kota Sawahlunto - Marrini, Liza; Thahar, Harris Effendi; Hamidin, Hamidin (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
The purpose of this study was to describe the meaning and value of moral education is contained in a figurative expression of Minangkabau society in the village of downstream talawi sub talawi Sawahlunto city. The data of this study is the figurative expression in the village of the downstream talawi subtalawi Sawahlunto city. Source of research data is the primary source of oral sources as spoken by the informant as the original speakers. Datawas collected using the methods and techniques refer to there cord and advanced engineering techniques as noted. The findings of the study include three things: (1) the meaning of figurative expression, the meaning is not true but there is no intention implied from the expression presented, with the aim that recipients do not feel offended expression, (2) the value of education, especially about the value of moral education that is useful in the association community life.